Elite player assessment of playing surfaces for football - Ronkainen, J.; Osei-Owusu, P.; Webster, J.; Harland, A.; Roberts, J. (Procedia Engineering, 2012)
Football (soccer) is a truly global game but for many of the 208 Fédération Internationale de Football Association (FIFA) Member Associations their climate is not suitable for growing good quality natural grass pitches with a low maintenance cost. As a consequence, for the 2004/2005 season, the laws of the game were modified to sanction the use of both natural and artificial surfaces. To date only one published study [1] has explored players` feelings towards the different surfaces used in football. The aim of this work was to identify relationships that players` perceive between the characteristics of a football pitch and the way in which the game of football is played. This paper reports the first in-depth elite player study utilising qualitative interview techniques to ascertain a wide range of user perceptions regarding playing surfaces for training and match play. 103 elite footballers consisting of 56 International players representing 4 continents playing at the highest level of football in France, Belgium and Holland were interviewed during the second half of the 2010/2011 season. The players participated in a 30 minute subject-led session occurring in English, French or Dutch utilizing a semi-structured approach in either focus group or individual interview format. A clustering approach was utilised to analyse the qualitative data collected, revealing compelling user insights into surfaces particularly in relation to ball characteristics, injury, player movement and style of play. For the purposes of this paper, a general overview is presented along with an in-depth analysis of ball interactions with the pitch. The output of this research will help guide future research and development in the football surface industry.